Looking Beyond School Walls: An Environmental Scan of Minneapolis Public Schools, 2004-2008 - Nicola A. Alexander; Wonseok Choi (Arizona State University, 2015)
We provide an expanded environmental scan to assess the strengths, weaknesses, opportunities, and threats (SWOT) faced by education communities. Grounded in the literature, we identified 48 indicators and grouped them into 6 broad categories: (1) budget levels, (2) funding patterns, (3) community needs, (4) external economic conditions, (5) political culture, and (6) children outcomes. We then created sub-categories for each of these six groupings based on whether the data came from school reports, non-school, governmental data, or not-for-profit entities. From these data, we developed a template with strategic guidelines for education leaders in varying environmental contexts. The discussion integrates school finance, fiscal condition analysis, leadership and organizational research to develop a framework that is then applied to the Minneapolis Public Schools for school years 2004 through 2008. The retrospective examination supports the utility of the strategic guidelines offered in the framework. Education leaders found a mixed educational climate in Minneapolis Public Schools for the years examined. There was cause for concern in the declining revenues for children services by other governmental agencies and increasing numbers of schools not making annual yearly progress. However, there were also opportunities apparent in the number of schools that offered International Baccalaureate and other rigorous programs and the support of schools as indicated by passage of local referenda.